Field-of-view correction in a VR HMD display with varifocal optics - Piszczek, Marek; Suchecki, Kacper; Kucharczyk, Aleksandra; Pomianek, Mateusz; Maciejewski, Marcin; Jodłowski, Leon; Krukowski, Piotr (Photonics Letters of Poland, 2022)
Nowadays, we observe a progressive increase amount of virtual technologies application. VR devices, i.e. HMDs, are still struggling with the VAC. It is possible to “implement” the accommodation mechanism in HMDs using a varifocal system. By using focus tuneable lenses, we achieve high speed and smoothness of displacement of the virtual image plane. This solution involves also unfavourable changes of geometrical parameters of the projected image i.e. change in magnification. This can be solved by software modification parameters of the virtual camera. In this paper, the developed construction of varifocal HMD is presented, including the method of maintaining the constancy magnification. Full Text: PDF References Y-J. Wang , Y-H. Lin, "Liquid crystal technology for vergenceaccommodation conflicts in augmented reality and virtual reality systems: a review", Liq. Cryst. Rev. 9. 35 (2021). CrossRef P.P. Monticone, M. Menozzi, M. Schlup, "Instrument for high-speed recording of accommodation of the human eye", Biomed. Tech. 55: 83 (2010). CrossRef G. Kramida, "Resolving the vergence-accommodation confict in headmounted displays", IEEE Trans. Vis. Comput. Graph. 22, 1912 (2016). CrossRef S. Shiwa, K. Omura, and F. Kishino, "Proposal for a 3-D display with accommodative compensation: 3DDAC," J. Soc. Inf. Disp. 4, 255 (1996). CrossRef K. Rathinavel, G. Wetzstein, H. Fuchs, "Varifocal Occlusion-Capable Optical See-through Augmented Reality Display based on Focus-tunable Optics," IEEE Trans. Vis. Comput. Graph. 25, 3125 (2019). CrossRef